Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-09-17T20:26:00+02:00
(5x - 3)(5x + 3) - (x - 2)²
= 25x² - 9 - (x² - 4x + 4)
= 25x² - 9 - x² + 4x - 4
= 24x² + 4x - 13

(5x + 1)² - (2x - 3)²
= 25x² + 10x + 1 - (4x² - 12x + 9)
= 25x² + 10x + 1 - 4x² + 12x - 9
= 21x² + 22x - 8
merci beaucoup
De rien! =)
tu peux m'aider pour mon autre exercice stp j'arrive pas non plus? :/
2014-09-17T20:30:50+02:00

Bonsoir


C(x)=(5x-3)(5x+3)-(x-2)²

C(x) = (5x)² - 3² - (x² - 4x + 4)

C(x) = 25x² - 9 - x² + 4x - 4

C(x) = 25x² - x² + 4x - 9 - 4

C(x) = 24x² + 4x - 13


D(x) = (5x+1)² - (2x-3)²

D(x) = (25x² + 10x + 1) - (4x² - 12x + 9)

D(x) = 25x² + 10x + 1 - 4x² + 12x - 9

D(x) = 25x² - 4x² + 10x + 12x + 1 - 9

D(x) = 21x² + 22x - 8